The Efektivitas Model Project Based Learning (PJBL) Berbasis Science Technology Engineering and Mathematics (STEM) Terhadap Kemampuan Berpikir Kreatif Matematis Siswa - Rahmawati, Dewi; Yuliardi, Ricki (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research is to find out how effective a STEM (science, technology, engineering, and math) project-based learning model is on students' ability to think creatively about opportunity material. This research is a type of quasi-experimental research with a one group pretest-posttest design. This research involved class VIII students at MTs Negeri 2 Kuningan. In this research, purposive sampling was used. Two classes VIII-H were selected as control classes and two classes VIII-I were selected as experimental classes, each with a total of 30 students. The data collection method used is to use a test instrument that focuses on creative indicators in the form of an essay consisting of five numbers. The research results show that students' mathematical creative thinking abilities vary from student to student